Genomic Insights into Neofusicoccum laricinum: The Pathogen Behind Chinese Larch Shoot Blight - Jialiang Pan; Zhijun Yu; Wenhao Dai; Chunhe Lv; Yifan Chen; Hong Sun; Jie Chen; Junxin Gao (Journal of Fungi)
Larch shoot blight, caused by the fungus Neofusicoccum laricinum, threatens larch (Larix spp.) forests across northeastern China, jeopardizing both timber productivity and ecological stability. This study aimed to investigate the genomic diversity, population structure, and potential adaptive mechanisms of N. laricinum across contrasting climatic regions. To achieve this, we conducted whole-genome resequencing of 23 N. laricinum isolates collected from three major provinces—Heilongjiang, Inner Mongolia, and Jilin—that represent distinct climatic zones ranging from cold-temperate to relatively warmer regions. We identified ~219.1 K genetic variants, offering a detailed portrait of the pathogen’s genomic diversity. Population structure analyses, including principal component analysis and phylogenetic tree, revealed clear genetic differentiation aligning with geographic origin and climate. Functional annotation (GO and KEGG) highlighted enrichment in metabolic, stress-response, and membrane transport pathways, suggesting potential adaptation to varied temperature regimes and environmental pressures. Moreover, region-specific variants—particularly missense and stop-gain mutations—were linked to genes involved in ATP binding, oxidoreductase activity, and cell division, underscoring the fungus’s capacity for rapid adaptation. Collectively, these findings fill a critical gap in the population genetics of N. laricinum and lay a foundation for future disease management strategies to larch shoot blight under changing climatic conditions.